2013
DOI: 10.1177/0218492312472688
|View full text |Cite
|
Sign up to set email alerts
|

Glomus tumor of the mediastinum

Abstract: Glomus tumors are rare benign myoepithelial neoplasms that can present with intractable pain. We report the case of a 59-year-old gentleman who presented with upper abdominal and chest pain caused by a posterior mediastinal glomus tumor arising from the spinal column, which required surgical resection. As glomus tumors usually develop in the limbs, this case highlights the complexity of diagnosis and treatment of glomus tumors when they present in rare locations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Clinically, this type of tumor is usually benign, and malignant cases have rarely been reported [ 13 ]. Additionally, mediastinal glomus tumors, first described in 1949, are extremely rare [ 2 ]; only five cases have been described in the English literature [ 1 - 3 , 8 , 9 ]. This is the sixth case of a glomus tumor in the mediastinum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, this type of tumor is usually benign, and malignant cases have rarely been reported [ 13 ]. Additionally, mediastinal glomus tumors, first described in 1949, are extremely rare [ 2 ]; only five cases have been described in the English literature [ 1 - 3 , 8 , 9 ]. This is the sixth case of a glomus tumor in the mediastinum.…”
Section: Discussionmentioning
confidence: 99%
“…Glomus tumors located in the mediastinum are extremely rare, and only five cases have been reported in the English literature [ 1 - 3 , 8 , 9 ]. We encountered a case of mediastinal glomus tumor in a 21-year-old woman, and reviewed the clinicopathologic characteristics of this case and previous mediastinal glomus tumor cases.…”
mentioning
confidence: 99%
“…These tumors usually occur in the subcutaneous region of distal extremities. Few cases of mediastinal pericytic neoplasms have been reported and mediastinal glomus tumors have been reported to be the most common tumor type among them 3–7 . In addition, most pericytic neoplasms, such as glomus tumor, are localized and resectable; however, in the present case, the tumor atypically invaded the esophagus and bronchus.…”
Section: Discussionmentioning
confidence: 52%
“…However, these tumors are rarely found in the mediastinum. A survey of the literature revealed that only seven cases have been previously described in the English literature [28]. According to the previous literature, the major symptom that is associated with this disease is chest pain or dyspnea.…”
Section: Discussionmentioning
confidence: 99%